The first Christian communities, 32-380 CE - Salisbury, Joyce E., author.
1 online resource
Keywords: "This concise history of how the Christian Church grew between 32 and 380 focuses on the anonymous Christians who formed diverse congregations as they guided their communities through the age of the Apostles, violent martyrdoms, and to the establishment of the Roman Church. Readers will understand why people converted to Christianity in the first three centuries and learn about the rich diversity of the early church as people interpreted the new religion in different ways. This book explores how Christian interactions with the Roman empire led to violent persecutions and martyrdoms, and eventually the fourth-century establishment of the top-down Roman Church. Readers also become familiar with Christian texts during this period - some became Scripture and some were rejected, but all were written to make sense of the Jewish and Christian experience in the Roman Empire. These written memories shaped the future of the church. It also explores how early Christian lives were shaped by the religious rituals and preaching of their new and changing faith. In addition, maps, illustrations, and charts of Christian texts help tell this fascinating story. The First Christian Communities, 32 - 380 CE is an accessible and valuable resource suitable for students working on Christian history, and Roman and Late Antique social, political and religious history, as well as general readers who are interested in the origins of Christianity"--